The Political Economy of Modern Iran - Katouzian, Homa. author. aut Link
X, 389 p.
Keywords: Visit the Unspun website which includes Table of Contents and the Introduction. The World Wide Web has cut a wide path through our daily lives. As claims of "the Web changes everything" suffuse print media, television, movies, and even presidential campaign speeches, just how thoroughly do the users immersed in this new technology understand it? What, exactly, is the Web changing? And how might we participate in or even direct Web-related change? Intended for readers new to studying the Internet, each chapter in Unspun addresses a different aspect of the "web revolution"--hypertext, multimedia, authorship, community, governance, identity, gender, race, cyberspace, political economy, and ideology--as it shapes and is shaped by economic, political, social, and cultural forces. The contributors particularly focus on the language of the Web, exploring concepts that are still emerging and therefore unstable and in flux. Unspun demonstrates how the tacit assumptions behind this rhetoric mustbe examined if we want to really know what we are saying when we talk about the Web. Unspun will help readers more fully understand and become critically aware of the issues involved in living, as we do, in a wired society. Contributors include: Jay Bolter, Sean Cubitt, Jodi Dean, Dawn Dietrich, Cynthia Fuchs, Matthew Kirschenbaum, Timothy Luke, Vincent Mosco, Lisa Nakamura, Russell Potter, Rob Shields, John Sloop, and Joseph Tabbi.